VEGETATION SPECIES ABUNDANCE IN MANGROVE ECOSYSTEM OF PASIR MENDIT AT BOGOWONTO LAGOON KULON PROGO YOGYAKARTA - Maizer Said Nahdi; Ardyan Pramudya Kurniawan (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
This research was conducted on Pasir Mendit, Bogowonto Lagoon. Pasir Mendit, Bogowonto Lagoon is one of unique beaches in Indonesia, with sand du-nes that protecting the beach from Indian Ocean €™s pounding waves. The purpose of this research is to shows the relation between the environmental fac-tors and the abundance of vegetations in the mangrove €™s ecosystem. Quadrates method were used for collecting the data, by making several plots of the study of growth forms. Connonical Correspondence Analysis (CCA) were used to analyze the correspondential relationship between vegetation and the environmental factors. The result of this research shows that there are 19 species of mangroves and its associates and unity. All of the locations are colo-nized by Acanthus ilicifolius bushes and Derris heterophylla woody climber, which is the r-strategy, with high level of density. Sonneratia alba and Rhi-zophora mucronata is the dominating species in all locations with varied abundance and importance value. This would be linked with the relatively high concentration of C organic, NO3 and SO4. The presence of Acanthus ilifolius and Derris heterophylla shows that the mangrove ecosystem of Men-dit has suffered from destructions. With the existence of mangrove in Bogowonto Lagoon, the place is suggested to be a conservation location model for other lagoons in Yogyakarta and Central Java.